Evaluating Asian swap arrangements - Joshua Aizenman; Yothin Jinjarak; Donghyun Park (Asian Development Bank Institute (ADBI), 2011)
Motivated by the unprecedented rise of swap agreements between the central banks of developed economies and their developing economy counterparts, this paper evaluates Asian swap arrangements and their association with the build-up of foreign reserves prior to the 2008-2009 global financial crisis. The evidence suggests that there is a limited scope for swaps to substitute for reserves. Furthermore, the selectivity of the swap lines indicates that only countries with significant trade and financial linkages can expect access to such ad hoc arrangements, on a case by case basis. Moral hazard concerns suggest that the applicability of these arrangements will remain limited. However, deepening swap agreements and regional reserve pooling arrangements may weaken the precautionary motive for reserve accumulation.
Keywords: F15; F31; F32; 330; Swap; Währungsreserven; Reservewährung; US-Dollar; Finanzmarktkrise; Wechselkurspolitik; Südkorea